Dinâmica do carbono orgânico em cronossequências de uso do solo no cerrado mineiro: mudanças nos estoques e simulação com o modelo Century - Juliana Martins Ribeiro (2020)
The growing need for food has generated demands for the expansion of new agricultural areas. The replacement of degraded areas, with low C stocks, with more sustainable management systems presents as a viable alternative to promote improvements in soil quality and increase in soil organic carbon (SOC), since 60% of pastures in the Brazil are in some stage of degradation. The introduction of systems that integrate several agricultural components in the same area, such as agrosilvopastoral systems, increases the SOC accumulation capacity and the potential for reducing greenhouse gas (GHG) emissions. Given the above, the objective of this study was to evaluate the carbon (C) and nitrogen (N) stocks of the soil and the humic fractions of the soil organic matter (SOM), in addition to simulating and designing future scenarios on the dynamics of the SOC in two chronosequences of land use in the Cerrado of Minas Gerais. The chronosequences of land use were composed of native vegetation (NV), degraded pasture (DPA) and crop-livestock-forest integration system (ICLF) and monoculture of Urochloa brizantha 'Marandu' (MAR) in Cerrado-Forest transition areas Semideciduous Seasonal and Cerrado-Atlantic Forest in Minas Gerais. For data analysis, it was used the t test at 5% probability (article 1), non-parametric statistics applying the Kruskal-Wallis test (p <0.05) (article 2) and the test t 10% probability (article 3) using software R. The ICLF systems presented an increase in soil carbon stocks, ranging from 1.44 Mg ha-1 ano-1 to 2.17 Mg ha-1 ano-1 . Increases in N stocks and C levels of soil humic fractions were observed with the introduction of ICLF systems in the two evaluated sites. The results of this study proved that there were improvements in soil quality and in C stocks after the change of land use of degraded pastures in ICLF systems and well-managed pasture monoculture. Additionally, it was observed an isotopic enrichment of 13C in the superficial layers of the soil promoted by the cultivation of grasses (species C4), indicating that these systems promote the accumulation of C in the soil over the driving time. The results showed that the Century model reliably simulated the SOC stocks of the two chronosequences. The model predicted an increase in SOC by converting the DPA system (46.04 Mg ha-1) into ICLF systems (54.94 Mg ha-1) in the chronosequence of Francisco Sá - MG and DPA system (42.38 Mg ha-1) in ICLF systems (51.71 Mg ha-1) in chronosequence of Curvelo - MG in the short, medium and long term, showing that the intensification of these systems in degraded areas, mainly in soils with clay texture, contributes to the accumulation of SOC and can be used as a model for adaptation and mitigation of climate change in the transition regions of the Cerrado of Minas Gerais.